(3GdUjOfI aj GdWHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdUjOfI CYQa ef GdUjOdI , hGdUjOGfi CYQa ef GdUjOfGfi, hgh GdeMJQa HLeY GdCOhjI Ydi CMeO UhQgG hENJjGQ GdGLhO ef GfhYgG s
(3BNQgG (B:s
(3jfJhf LGdjfS (B: (3hgh GdSPGH GdLHdi, hUfYg gh GdJaSjG jfYhf(B: (3h GdJaSjG, MSHfG Gddg hfYe GdeYjf GdMeO ddg TcQkG s
(3fSNI KGfjIs
(3hYdi GdfSNINW GdCH CfSJGS GdcQedis
(3hLGA HBNQgG cJGH ef OcJhQ GdGdeGfj aQJRcQfchs
(3hbO fbd MQai GdLje hGdbGa HGdYQHjI Yf GdaQfSjI hHBNQgG CSeGA ehGO NW eNGda eQJHI CHLOjkG ef hQbI (B219 (3Edi (B273 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
Keywords: (3GdWHs